KREATIVITAS GURU DALAM EVALUASI HASIL BELAJAR PENDIDIKAN AGAMA ISLAM PADA SISWA DI UPT SPF SD INPRES MALLENGKERI BERTINGKAT I - Jannah, Miftahul; Abdullah, Ahmad; Sijal, Mutakallim (Jurnal Kinerja, 2024)
The purpose of this study was to determine the learning outcomes of Islamic religious education in students and the creativity of Islamic religious education teachers in evaluating Islamic religious education learning outcomes at UPT SPF SD Inpres Mallengkeri Bertingkat I as well as the factors that hinder and support the creativity of PAI teachers in evaluating Islamic religious education learning outcomes. The type of research used is descriptive qualitative method. Data collection techniques in this research are observation, interview, and documentation. The data sources in this research are primary and secondary data sources. While the object of this research is the Islamic Religious Education teacher of UPT SPF SD Inpres Mallengkeri Bertingkat I. The results showed that the learning outcomes of Islamic Religious Education at the school were not significant. The results showed that the PAI learning outcomes at UPT SPF SD Inpres Mallengkeri Bertingkat I were quite good because the scores obtained by students were able to achieve scores above the predetermined passing standard of 70-75. Teachers' creativity in evaluating learning outcomes obtained confirmation that creativity is determined by the factor of choosing the right method such as the use of effective methods and good class management, while the factors that hinder creativity are the lack of student awareness of the importance of evaluation and factors that support creativity are good school conditions and teachers who always provide guidance before the evaluation